2013
DOI: 10.1038/ijo.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and extremity muscle mass in overweight and obese women

Abstract: Obesity disproportionately affects women, especially those of African descent, and is associated with increases in both fat and muscle masses. Although increased extremity muscle mass may be compensatory to fat mass load, we propose that elevated insulin levels resulting from diminished insulin sensitivity may additionally contribute to extremity muscle mass in overweight or obese women. The following measurements were performed in 197 non-diabetic women (57% black, 35% white; age 46±11 years [mean±SD], BMI ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…On the other hand, hyperinsulinemia in overweight/obese subjects is associated with increased extremity muscle mass, which is partially reversible with reduction in fasting insulin concentration, consistent with the stimulatory effects of insulin on skeletal muscle after treadmill exercise [575]. It is well known that insulin stimulates glycogen synthase (GS) through dephosphorylation of serine residues, and this effect is impaired in skeletal muscle from insulin-resistant obese subjects.…”
Section: Skeletal Musclementioning
confidence: 67%
“…On the other hand, hyperinsulinemia in overweight/obese subjects is associated with increased extremity muscle mass, which is partially reversible with reduction in fasting insulin concentration, consistent with the stimulatory effects of insulin on skeletal muscle after treadmill exercise [575]. It is well known that insulin stimulates glycogen synthase (GS) through dephosphorylation of serine residues, and this effect is impaired in skeletal muscle from insulin-resistant obese subjects.…”
Section: Skeletal Musclementioning
confidence: 67%
“… Fukushima et al (2016) using a 6-month mixed-exercise and nutritional intervention in 92 middle-aged obese women found that fasting insulin and glucose decreased in those whose SM mass index (kg/m 2 ) also decreased over the course of the intervention ( Fukushima et al, 2016 ). Leon et al (2013) also illustrated this point in 132 middle-aged women who participated in a 6-month diet and exercise program ( Leon et al, 2013 ). Before the intervention, the authors noted that appendicular SM mass was proportional to the level of obesity and was also proportionally related to fasting insulin levels.…”
Section: Narrative Literature Reviewmentioning
confidence: 99%
“…As obesity develops, there is an almost 1 : 1 increase in fat and lean mass . A significant portion of the increase in weight occurs in the form of skeletal muscle . Consequently, disposal of excess energy by more lean body mass could help to buffer the caloric overload in obese individuals.…”
Section: Overnutrition Vs Adipositymentioning
confidence: 99%